2016
DOI: 10.1111/1753-6405.12538
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the relationships between body dissatisfaction, quality of life and psychological distress

Abstract: Background: Body dissatisfaction is associated with impairment in women's quality of life (QoL). To date, research has not examined the relationship between body dissatisfaction and men's QoL, or sex differences in this relationship. Methods:A community sample of 966 males and 1,031 females living in Australia provided information about their body dissatisfaction, mental health and physical health-related QoL, and eating disorder symptoms. Data were analysed using three hierarchical multiple regressions and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
128
2
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 194 publications
(148 citation statements)
references
References 35 publications
12
128
2
6
Order By: Relevance
“…Finally, the majority of studies in the area have been limited to female participants. Although the prevalence of eating disorders is higher among women than among men (Eisenberg, Nicklett, Roeder, & Kirz, ; Kjelsås, Bjørnstrøm, & Götestam, ), research with community samples tends to find smaller differences (Striegel‐Moore et al, ), and significant proportions of both men and women experience body dissatisfaction (Fallon, Harris, & Johnson, ; Griffiths et al, ). Furthermore, with respect to the components of our model, there are also no clear gender differences.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the majority of studies in the area have been limited to female participants. Although the prevalence of eating disorders is higher among women than among men (Eisenberg, Nicklett, Roeder, & Kirz, ; Kjelsås, Bjørnstrøm, & Götestam, ), research with community samples tends to find smaller differences (Striegel‐Moore et al, ), and significant proportions of both men and women experience body dissatisfaction (Fallon, Harris, & Johnson, ; Griffiths et al, ). Furthermore, with respect to the components of our model, there are also no clear gender differences.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in body image are increasingly being recognised as a public health concern, being associated with poor quality of life (Griffiths et al, 2016) as well as increased risk for a range of difficulties, most notably eating disorders, but also depressive symptoms, overweight, and unhealthy weight control behaviours, such as cigarette smoking (Field et al, 2005; Loth, Watts, Van Den Berg, & Neumark-Sztainer, 2015; Patalay, Sharpe, & Wolpert, 2015; Rohde, Stice, & Marti, 2015; Sonneville et al, 2012; Sonneville et al, 2015). Despite the centrality of body image disturbances in models of risk and maintenance (e.g., Fairburn, Cooper, & Shafran, 2003; Stice, Gau, Rohde, & Shaw, 2017), and in diagnostic criteria for eating disorders (American Psychiatric Association, 2013), this construct remains relatively loosely conceptualised, with terms often used interchangeably, or captured under umbrella concepts, such as ‘weight and shape concerns’ (e.g., La Mela et al, 2015; Murphy, Dooley, Menton, & Dolphin, 2016).…”
mentioning
confidence: 99%
“…Discrepancies between current body weight and desirable weight has been linked to discrimination, internalized stigma and body image trepidations [7]. An extensive systematic review suggests that those with high levels of body dissatisfaction have a range of cognitive biases to appearance-related stimuli [4]. Furthermore, recent research has shown that higher body dissatisfaction is associated with poorer physical and mental health-related quality of life as well as greater psychological distress [4].…”
Section: Discussionmentioning
confidence: 99%
“…The mass media has been consistently implicated in influencing beliefs about ideal body size and shape with recent research reporting adverse effects in young people [4,11] and women [4,6]. Body dissatisfaction has become a public health concern [4], although evidence to support this claim in the Middle East region is sparse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation